Incremental approach for Continuous k-Nearest Neighbours queries on road. (15th May 2008) - Khayati, Mourad; Akaichi, Jalel
With the integration of wireless communication and positioning technologies, Location Based Services (LBSs) contribute to the enhancement of spatial databases applications and the efficiency of pervasive systems. This is ensured by providing efficient responses for location dependent queries triggered by mobile users. In this paper, we propose a new approach based on Delaunay Triangulation (DT) and the determination of Nearest Neighbors (NNs), which constitutes an important class of problems in LBS. We show that our approach, applied on road networks, is able to establish the Continuous k-Nearest Neighbors (CkNNs) while taking into account the dynamic changes of locations from which the queries are issued.